2018
DOI: 10.1097/brs.0000000000002214
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Spinal Injuries in Northern Finland

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 26 publications
6
22
1
1
Order By: Relevance
“…4,5,10 Like other developing countries there is tremendously increase in number of vehicle which is not proportion to quality of road in India further raises the incident in of roadtraffic accident in younger group of people. In our study lumber spinal column was fractured (55%) followed by thoracic spine (22.78%) and cervical spine injuries noted in (20.8%) that results are similar to other studies like ville niemi et al 15 The dorsal spine is fixed and less mobile because of rib cage as compared to lumbar spine which is very mobile portion of spine. 14 The sudden transition from fixed to mobile portion makes dorso-lumbar area as a precarious site for TSI.…”
Section: Discussionsupporting
confidence: 90%
“…4,5,10 Like other developing countries there is tremendously increase in number of vehicle which is not proportion to quality of road in India further raises the incident in of roadtraffic accident in younger group of people. In our study lumber spinal column was fractured (55%) followed by thoracic spine (22.78%) and cervical spine injuries noted in (20.8%) that results are similar to other studies like ville niemi et al 15 The dorsal spine is fixed and less mobile because of rib cage as compared to lumbar spine which is very mobile portion of spine. 14 The sudden transition from fixed to mobile portion makes dorso-lumbar area as a precarious site for TSI.…”
Section: Discussionsupporting
confidence: 90%
“…These indicated that the prevention of falls and other low energy trauma, especially in the elderly, may reduce the incidence of spinal fractures dramatically. [1] Elderly might benefit from a directed assessment and modification of environmental hazards (e.g., problems with building design, handrails, surfaces, changes in elevation and lighting) to reduce the incidence of falls and traumatic spinal fractures. [20] In addition, by encouraging scientific, reasonable and effective sports therapy which can be used as an effective method to prevent both osteoporosis and falls in elderly, [21] might be another method to decrease the incidence rate of traumatic spinal fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic spinal injuries are one of the most common causes of major morbidity and mortality. [1] Spinal and spine-related injuries, which are common in trauma, have the poorest functional outcomes and the lowest rates of return to work among all major organ injuries. [2] One of the first steps in preventing this injury is the collection and analysis of data to help define the problem and identify possible risk factors in various populations.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic injuries are mostcommon in the younger working population but they arealso high among the older population [2]. Spinal column injuries are rare, but they can cause high mortality andmorbidity rates with heavy burdens and lifelong social, financial, and personal problems and even permanent disabilities [3]. Traumatic spinal column injuries are alsohigh in low socio-economic areas due to frequent use of motorcycles, lack of sufficient immunity, and absence of adequate infrastructures.…”
Section: Introductionmentioning
confidence: 99%